Spectral and Cathodoluminescence Decay Characteristics of the Ba1−xCexF2+x (x = 0.3–0.4) Solid Solution Synthesized by Precipitation from Aqueous Solutions and Fusion - Sergey V. Kuznetsov; Darya S. Yasyrkina; Damir T. Valiev; Sergey A. Stepanov; Alexander A. Alexandrov; Sergey Kh. Batygov; Valeriy V. Voronov; Vasilii A. Konyushkin; Andrey N. Nakladov; Julia A. Ermakova; Pavel P. Fedorov (Photonics, 2023)
Single-phase samples of the Ba1−xCexF2+x solid solution (x = 0.3–0.4) were synthesized by directional crystallization in the form of single crystals and by co-precipitation from aqueous nitrate solutions using potassium fluoride as a fluorinating agent in the form of nanopowders. The cathodoluminescence of the pressed powder samples was studied in comparison with the BaF2: Ce single crystals in 250–460 nm (2.7–5 eV) spectral range upon excitation by an electron accelerator. The cathodoluminescence spectra of the samples revealed a wide band in the range of 3.0–4.0 eV, which consists of two typical components of Ce3+ with decay time 23 ns in the case of single crystals and three decay times 27 ns, 140–170 ns, and ~600 ns in the case of pressed powders. The decay time of the short-wavelength component (27 ns) in the case of pressed powders is close to the lifetime of the excited state of the Ce3+ ion. The developed X-ray phosphors can be applied for embedding in diamonds for diamond–nanoparticle composite preparation.